FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI LEMBAGA PENYIAR PUBLIK TVRI STASIUN NTT - Simon Sia Niha; Henny Angri Manafe; David Manafe (Jurnal Administrasi Bisnis, 2021)
This research aims to analyze the effect of information technology, work environment, work motivation, OCB, and social support on employee performance moderated by social support at the TVRI Public Broadcasting Institute. This research uses a quantitative survey. The population and sample in this research consists of 61 people. The data used are primary and secondary data. Data collection methods of this research are interviews, questionnaires and documentation. The data are analyzed using descriptive statistical analysis techniques and inferential statistical analysis. The results of the inferential statistical analysis shows that information technology has a significant effect on employee performance, the work environment has no significant effect on employee performance, work motivation has a significant effect on employee performance and OCB has no significant effect on employee performance. The results of the moderation test shows that social support is able to moderate information technology on employee performance, social support does not moderate the effect of the work environment on employee performance, social support moderates the effect of motivation on employee performance and social support moderates the effect of OCB on employee performance.